Increased Interleukin-6 as Inï¬‚ ammatory Response and Magnesium Deï¬ ciency in Pre-dialysis Chronic Kidney Disease of Indonesian Children - Kardani, Astrid Kristina; Soemyarso, Ninik Asmaningsih; Aras, Jusli Aras; Prasetyo, Risky Vitria; Noer, Mohammad Sjaifullah (Institute of Topical Disease Universitas Airlangga, 2021)
Chronic kidney disease (CKD) is a serious health problem in children, with increasing morbidity and mortality rates throughout the world. Children with CKD tend to experience magnesium (Mg) deï¬ ciency that can stimulate an inï¬‚ ammatory response in the body. One of the inï¬‚ ammatory responses is an increase of Interleukin-6 (IL-6). Study to analyze the correlation between Mg and IL-6 in pre-dialysis CKD children. The methods a cross sectional study was conducted in Dr Soetomo General Academic Hospital from November 2018 to April 2019. Children with pre-dialyis CKD were included in this study. Variables of serum Mg level (mg/dL) and inï¬‚ ammatory marker (IL-6) were measured from the blood and analyzed by ELISA method. The correlation between Mg and IL-6 was analyzed with Spearman's correlation test with p <0.05. Result a total of 47 children (27 boys vs 20 girls) between 3 months to 18 years old, with pre-dialysis CKD and no history of magnesium supplementation were included. The primary disease that causes of CKD were lupus nephritis (38.3%), nephrotic syndrome (23.4%), urologic disorder (23.4%), tubulopathy (10.6%) and others (4.3%). The average IL-6 level was 55.42±43.04 pg/dL and Mg level was 2.06±1.54 mg/dL. There were no signiï¬ cant correlation between IL-6 level and Mg level with staging of CKD and duration of illness (p>0.05), but there was a signiï¬ cant correlation between serum Mg level and IL-6 level (r=-0.748; p<0.001). Magnesium levels have a signiï¬ cant inverse correlation with IL-6 levels in pre-dialysis CKD children. The lower the Mg levels in the blood, the higher IL-6 levels and vice versa.